The relationship between melatonin levels and insulin resistance in patients with type 2 diabetes mellitus under chronic war stress - M.I. Bobryk; V.S. Yuzvenko; D.Y. Malyi; Y.I. Komisarenko (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. In recent years, information has emerged about the relationship between melatonin and insulin and the expression of melatonin receptors in the central nervous system. The severity of melatonin deficiency in patients with type 2 diabetes mellitus (T2DM) may vary during the war. The aim of the study was to assess the changes in nocturnal melatonin levels and its relationship with the severity of insulin resistance in patients with T2DM during the full-scale war in Ukraine compared to the pre-war state. Materials and methods. In 2021–2024, a prospective study was conducted, which included patients aged 19–75 years with T2DM in a state of compensation (glycated hemoglobin level ≥ 6.5 and < 8.0 %). The exclusion criteria were: T2DM with severe chronic complications, glycated hemoglobin level < 6.5 %, acute inflammatory processes, oncological diseases, body mass index ≥ 40 kg/m2, taking antidepressants, melatonin preparations less than 2 months before the study. The study involved 404 patients with T2DM from different regions of Ukraine. Laboratory assessment of melatonin levels in saliva was performed by solid-phase enzyme-linked immunoassay. Results. The frequency of melatonin deficiency in patients with T2DM increased from 54.3 % in 2021 to 70.9 % in 2024. On the background of an increase in the number of patients with melatonin deficiency, there is a significant increase among them of individuals with an elevated HOMA index, from 12.5 % in 2021 to 47.2 % in 2024. Changes in the distribution of results according to the HOMA index on the background of melatonin deficiency indicate an increase in the relative risk of detecting a HOMA index above normal in the group with melatonin deficiency by 6.2 times in 2024 (odds ratio 6.2, 95% confidence interval: 1.9–26.5). Conclusions. The impact of war stress and insomnia are more significant risk factors for pathological levels of the HOMA index on the background of melatonin deficiency. Patients with T2DM are recommended to assess the level of melatonin in saliva with its further correction in those with melatonin deficiency, since such correction can lead to a decrease in insulin resistance and improvement of carbohydrate metabolism.